PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL - Stephanie Angel Gultom; Roida Nababan (Jurnal Keluarga Sehat Sejahtera, 2025)
The rapid development of information technology has provided ease of communication, but on the other hand it has caused new legal problems, one of which is the crime of defamation through social media. This crime has a serious impact on a person's reputation, honor, and dignity because the dissemination of information in the digital space is fast, widespread, and difficult to delete. This study aims to analyze the form of legal protection for victims of criminal defamation through social media as well as the mechanism of restoring the victim's good name in the Indonesian legal system. The method used is normative juridical with a statutory and conceptual approach, by examining the Criminal Code (KUHP) and Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) as the legal basis. The results of the study show that legal protection for victims is carried out through three main forms, namely preventive, repressive, and then rehabilitative. In addition, this study also examines what the mechanism is like in restoring good name from the crime of defamation through social media which can be done through criminal channels (Restorative Juctice) and civil channels (restitutio in integrum). Thus, it can be concluded that legal protection for victims of defamation on social media not only emphasizes the aspect of punishment, but also the restoration of dignity and social justice through synergy between law enforcement officials, advocates, and digital platform providers